Status of pedagogical practices in Somaliland higher education institutions - Gulled Mohamed Yasin; Rachel Monde Kabeta (Journal of Education and Learning (EduLearn), 2023)
Recently, there has been a concern in many parts of the world about the teaching strategies employed at higher education institutions (HEI). Empirical evidence shows that pedagogical practices affect the student engagement and academic excellence. Despite progress on the new innovative pedagogies globally, Somaliland HEI are still struggling with the old didactic teaching method which impedes students lifelong learning and future endeavors. Traditional teaching methods of HEI in Somaliland prevented students to unleash their potentials. Guided by the human capital theory, this study examined the status of lecturers’ application to modern pedagogical practices. The 35 lecturers at the University of Hargeisa, Somalia from the different faculties who had received postgraduate diploma in education provided by the university participated in this study. Employed by micro-teaching observation protocol of quantitative research design, the study found out lecture method as the most prevalent in their teaching practicum, with very low student cognitive engagement, inconsistencies with the instructional behavior and inadequate instructional aids. The study therefore proposed a cooperative jigsaw method as a veritable strategy for effective classrooms and better student engagement. The study recommends Somaliland higher education to adopt the policies, guidelines and regulations that guide the universities across the country.